2013
DOI: 10.1007/s11626-013-9634-0
|View full text |Cite
|
Sign up to set email alerts
|

The oxidizing agent, paraquat, is more toxic to Wolbachia than to mosquito host cells

Abstract: Cultured cells provide an important in vitro system for examining metabolic interactions between the intracellular bacterium, Wolbachia pipientis, and its insect hosts. To test whether Wolbachia-associated changes in antioxidant activities could provide a tool to select for infected cells, we tested the effects of paraquat (PQ) on Aedes albopictus mosquito cells. Like mammalian cells, mosquito cells tolerate PQ over a wide range of concentrations, and for considerable lengths of time, depending on cell density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…To compensate for higher cell densities attained with antibiotic suppression of Wolbachia (Fallon et al . 2013a, b), cell counts were normalized by defining values for mimosine-free controls as 100% for each population. Visual inspection by microscopy indicated that the abundance of fluorescently stained Wolbachia appeared unaffected by mimosine (not shown), and metabolic activity assessed by MTT values of both control and mimosine-treated C/ w Str1 cells reached maximal levels at about 5 d after plating (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To compensate for higher cell densities attained with antibiotic suppression of Wolbachia (Fallon et al . 2013a, b), cell counts were normalized by defining values for mimosine-free controls as 100% for each population. Visual inspection by microscopy indicated that the abundance of fluorescently stained Wolbachia appeared unaffected by mimosine (not shown), and metabolic activity assessed by MTT values of both control and mimosine-treated C/ w Str1 cells reached maximal levels at about 5 d after plating (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we used Coulter cell counts, MTT assays and PCR reactions to demonstrate a reduction in Wolbachia levels in host cells exposed to the oxidizing agent, paraquat (Fallon et al, 2013b), and the riboflavin transport inhibitor, lumiflavin (Fallon et al, 2014). As a final check on the reliability of FC date, these experiments were repeated by quantifying WP and CP events.…”
Section: Resultsmentioning
confidence: 99%
“…In insect tissues, Wolbachia are pleomorphic in size and shape (Hertig, 1936) and cannot be physically separated from mitochondria (Sun et al, 2001), which have a DNA genome ~75-fold smaller than that of Wolbachia . Because Wolbachia are no longer recoverable by centrifugation after treatment with 2X PI-MM, presumably due to detergent-associated damage to the bacterial cell wall, we validated the presence of Wolbachia in the WP by showing that material from filtered cell culture supernatant recovered by centrifugation is associated with a cell-free WP with 99% of events in the lower left quartile of the SSlog/FL3 histogram (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations